Hepatitis B Virus Vaccination Status among the Students of Dhaka National Medical College - Salma, Umma; Sarwar, Golam; Sattar Sarker, Mohammad Abdus; Shamim Ahamed, Kazi (Journal of Dhaka National Medical College & Hospital, 2018)
Objective: To determine the Hepatitis B vaccination status among Medical students at Dhaka National Medical College. As well as to identify the reasons for non vaccination. Materials and Methods: It was a cross sectional survey conducted from 1st of September to 31st of October 2016 among 705 medical students from 1st to 5th year at Dhaka National Medical College using a pretested, self-administered, structured questionnaire with prior informed consent. Through the questionnaire the status of hepatitis B vaccination, and the reasons for vaccination as well as causes for not getting vaccination were assessed among the students. Result: The response rate of this survey was 96% where 82% were local students and 18% were foreign students. 399 (72%) local students and 102 (84%) foreign students were vaccinated. 93% local students and 100% of the foreign student completed their full dose of vaccine. The major reason for receiving vaccination among the local students was their parental effort (72%) and laziness (78%) was found as the main reason for non-vaccination. Foreign students who were vaccinated, the primary reason behind it was their parental effort (88%) and the main reason for non-vaccination was laziness (55%) which is similar as among the local students. Conclusion: Vaccination rate among medical students is not satisfactory. There is a definite lack of awareness regarding benefit of hepatitis B vaccination among them. Increasing awareness, increase in availability of hepatis B vaccination centers, reduce the cost of hepatis B vaccine and introduce the regulation of mandatory hepatitis B vaccination during medical admission may improve this situation. J. Dhaka National Med. Coll. Hos. 2018; 24 (01): 06-10